Current Progress and Future Perspectives of Electrolytes for Rechargeable Aluminum‐Ion Batteries. Issue 1 (15th April 2022) - Ma, Dongwei; Yuan, Du; Ponce de León, Carlos; Jiang, Zheng; Xia, Xin; Pan, Jiahong
Abstract : Aluminum‐ion batteries (AIBs) with Al metal anode are attracting increasing research interest on account of their high safety, low cost, large volumetric energy density (≈8046 mA h cm −3 ), and environmental friendliness. Specifically, the reversible Al electrostripping/deposition is achieved with the rapid development of room temperature ionic liquids, and rapid progress has been made in fabricating high‐performance and durable AIBs during the past decade. This review provides an integrated comprehension of the evolution of AIBs and highlights the development of various non‐aqueous and aqueous electrolytes including high‐temperature molten salts, room temperature ionic liquids, and gel–polymer electrolytes. The critical issues on the interplay of electrolytes are outlined in terms of the voltage window span, the effective ion species during charge storage (Al 3+ or Al x Cl y ‐ ) and their underlying charge transfer (e.g., interfacial transfer and diffusion), and the solid electrolyte interface formation and its role. Following the critical insight, future perspectives on how to practically design feasible AIBs are given. Abstract : Critical insight into the recent advances in the electrolytes for rechargeable aluminum‐ion batteries (AIBs) with future perspectives on how to practically design feasible AIBs.